Contemporary aspects on the immunopathogenesis of pemphigus group in the dog - PAPADOGIANNAKIS (E. Ι. ΠΑΠΑΔΟΓΙΑΝΝΑΚΗΣ) E. M. (Journal of the Hellenic Veterinary Medical Society, 2017)
Autoimmune diseases of the canine epidermis originate from the activation of the immune system against some adhesion molecules, which link the keratinocytes. Epidermal autoimmunity eventually induces acantholysis, which is thepathological hallmark of these skin diseases. In this review article, a thorough analysis of the immunopathogenesis for each of these skin diseases has been attempted along with the mechanisms that modulate the process of acantholysis. Epidermal autoimmune diseases in the dog include pemphigus foliaceus, vulgaris, panepidermal pustular, erythematosus, paraneoplastic and pharmaceutical. The recent advances in immunopathological and molecular techniques have markedly facilitated the understanding of their pathogenesis, thus giving the opportunity for the development of new therapeutic strategies that may lead to their successful treatment.